Graphene based Solution Gated Field-Effect Transistors (SGFET) for biosensors - Sarker, Abdullah Hossain; Tabassum, Maisha; Erfan, Nafis (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.